Paharpur alias Somapura Mahavihara : a world cultural heritage site - Haque, Enamul, 1936- (Studies in Bengal art series, 2014)
A comprehensive volume on Paharpur Site (Somapura Mahavihara), one of the best known Buddhist viharas in the sub-continent.